2016
DOI: 10.1093/mutage/gew042
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisandMycobacterium marinumnon-homologous end-joining proteins can function together to join DNA ends inEscherichia coli

Abstract: Mycobacterium tuberculosis and Mycobacterium smegmatis express a Ku protein and a DNA ligase D and are able to repair DNA double strand breaks (DSBs) by non-homologous end-joining (NHEJ). This pathway protects against DNA damage when bacteria are in stationary phase. Mycobacterium marinum is a member of this mycobacterium family and like M. tuberculosis is pathogenic. M. marinum lives in water, forms biofilms and infects fish and frogs. M. marinum is a biosafety level 2 (BSL2) organism as it can infect humans,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…brucei cells to treatment with DSB-inducing reagents (67). Since NHEJ is the most efficient DSBR pathway in mammalian cells, to improve DSBR efficiency in Leishmania and overcome the possible hindering effect of Ku70/80 on other DSBR pathways, it will be interesting to determine whether it is possible to reconstitute the NHEJ pathway in Leishmania by transgenic expression of ligase IV and XRCC4 from humans or other organisms, as in yeast and Escherichia coli, where the NHEJ pathway is reconstituted by the transgenic expression of mycobacterial Ku and ligase proteins (68, 69). In mammalian cells and yeast, the Rad52 protein plays a central role in HR and SSA, as it interacts directly with both RPA and Rad51 to promote the assembly of the Rad51 nucleoprotein on ssDNA and assist with the homology search and complementary ssDNA annealing (45).…”
Section: Discussionmentioning
confidence: 99%
“…brucei cells to treatment with DSB-inducing reagents (67). Since NHEJ is the most efficient DSBR pathway in mammalian cells, to improve DSBR efficiency in Leishmania and overcome the possible hindering effect of Ku70/80 on other DSBR pathways, it will be interesting to determine whether it is possible to reconstitute the NHEJ pathway in Leishmania by transgenic expression of ligase IV and XRCC4 from humans or other organisms, as in yeast and Escherichia coli, where the NHEJ pathway is reconstituted by the transgenic expression of mycobacterial Ku and ligase proteins (68, 69). In mammalian cells and yeast, the Rad52 protein plays a central role in HR and SSA, as it interacts directly with both RPA and Rad51 to promote the assembly of the Rad51 nucleoprotein on ssDNA and assist with the homology search and complementary ssDNA annealing (45).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that M. smegmatis Ku can bind to DNA without free ends and this property was attributed to its lysine-rich C-terminal extension ( 49 ). MmKu has a similar C-terminal extension ( 32 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear-targeted MtKu also attenuates homologous recombination in mammalian cells ( 31 ). Analogous to M. tuberculosis, M. marinum was recently shown to possess a proficient NHEJ system ( 32 ). We have determined that M. marinum Ku (MmKu) is expressed at a higher level than MtKu in bacterial ( 32 ) and mammalian cells (this study).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with the CRISPR system, HDR provides accurate and markerless target gene deletion, mutation, and insertion of foreign DNA sequences (Cobb et al, 2015). Alternatively, in some bacterial species such as Mycobacterium smegmatis, DSB can be repaired by the NHEJ system, which comprises an ATP-dependent DNA ligase and a Ku protein (Wright et al, 2017;Zheng et al, 2017). Unlike HDR, the NHEJ system does not require homologous DNA sequences for recombination, but directly joins the breaks, facilitating convenient gene deletion and insertion (Babynin, 2007).…”
Section: Introductionmentioning
confidence: 99%